HIV knowledge, risky behaviours and public health care services attendance among adolescents from the Grassroot soccer Zimbabwe programme - Mayibongwe Louis Mzingwane; Greanious Alfred Mavondo; Fennie Mantula; Claudinos Mapfumo; Calleta Gwatiringa; Bhekimpilo Moyo; Primrose Dube; Cynthia Nombulelo Chaibva (BMC, 2020)
Abstract Background Interventions aimed at improving accessing of health care services, including HIV testing, remain a priority in global HIV eradication efforts. Grassroot Soccer Zimbabwe (GRSZ) is an adolescent health organisation that uses the popularity of soccer to promote healthy behaviours. We assessed HIV knowledge levels, risky behaviours and attitudes in school going adolescents and young adults who attended GRSZ programmes and determined if HIV knowledge levels were associated with increased levels of accessing of health care services by youths. Methods This was a cross-sectional study carried out on 450 participants aged 13-30 years who attended at least one of the three programmes offered by GRSZ. Self-administered and self-reporting questionnaires were used to collect information on participants' demographics, knowledge on HIV and reproductive health, sources of information, access to HIV and reproductive health services and attitudes and risky behaviours. Results A total of 392 (87.1%) responses were received. High HIV and reproductive health knowledge levels were recorded (77.7%) on our scale with females recording higher levels (81.1%) than males (71.1%). The majority of participants (72%) indicated willingness to abstain from risky behaviours such as use of drugs and attending youth sex parties. However about 33.3% of the participants who had sexual intercourse reported having condomless sex. There was marginal association between high HIV and reproductive health knowledge levels and accessing health care services in the past 24 months (p = 0.045). Conclusions HIV and reproductive health knowledge levels were relatively high among adolescents and were associated with accessing health care services in the past 24 months. There however are some gaps associated with engaging in risky sexual behaviours such as condomless sex which could be addressed by using these findings to assist organizations working with adolescents, educators and policy makers in developing programmes that address adolescent sexual behaviours.